Perancangan Sistem Informasi Keuangan Pada Unit Koperasi Simpan Pinjam - Luki Hernando (Prodi Sistem Informasi Universitas Dharma Andalas, 2020)
Research by the author at Cooperative Center District aims to determine the presence of data processing system finance especially in terms of savings and loans, installment loans and data processing cooperative members that was running at Cooperative Center District. Therefore, by implementing a new system that can optimize data processing system of finance in the savings and loans unit and can improve employee performances and improve the quality of higher cooperative. The research was conducted by collecting data, direct observation, and laboratory research in designing computer programs and the preparation of reports. The importance of the conclusion, with this new system will be able to assist the employee in performing data processing of finance in the savings and loans unit Cooperative Center and can provide information and reports quickly and as required.